2012
DOI: 10.1088/0004-637x/755/1/34
|View full text |Cite
|
Sign up to set email alerts
|

The Hydromagnetic Interior of a Solar Quiescent Prominence. I. Coupling Between Force Balance and Steady Energy Transport

Abstract: This series of papers investigates the dynamic interior of a quiescent prominence revealed by recent Hinode and SDO/AIA high-resolution observations. This first paper is a study of the static equilibrium of the Kippenhahn-Schlüter diffuse plasma slab, suspended vertically in a bowed magnetic field, under the frozenin condition and subject to a theoretical thermal balance among an opticallythin radiation, heating, and field-aligned thermal conduction. The everywhereanalytical solutions to this nonlinear problem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 80 publications
4
23
0
Order By: Relevance
“…Alternative models include dynamic processes such as injection (e.g., Wang 1999;Chae et al 2001), levitation (e.g., Galsgaard & Longbottom 1999;Litvinenko & Wheatland 2005), and magnetothermal convection (e.g., Berger et al 2011;Low et al 2012aLow et al , 2012b. However, substantial work is needed to produce comparable, quantitative, timedependent predictions for other models of prominence plasma and magnetic structure (see Mackay et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative models include dynamic processes such as injection (e.g., Wang 1999;Chae et al 2001), levitation (e.g., Galsgaard & Longbottom 1999;Litvinenko & Wheatland 2005), and magnetothermal convection (e.g., Berger et al 2011;Low et al 2012aLow et al , 2012b. However, substantial work is needed to produce comparable, quantitative, timedependent predictions for other models of prominence plasma and magnetic structure (see Mackay et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although our numerical simulation does not include radiative cooling and thus cannot model the process of prominence formation, it is likely that the prominence plasma is co-spatial with the dense current layer (e.g., van Ballegooijen & Cranmer 2010; Low et al 2012). Our MHD simulation also does not model explicitly the background coronal heating but instead simply assumes a high temperature coronal plasma with an adiabatic index of γ = 1.1, without explicitly incorporating the coronal heating and radiative cooling processes.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their low temperature, prominences are made of partially-ionized plasma, with the ionization fraction of hydrogen characteristically 0.2 (Ruzdjak & Tandberg-Hanssen 1989;Engvold et al 1990;Labrosse et al 2010) in the centre of the dense prominence material. In prominences, it has been suggested that plasma is supported against gravity by the Lorentz force (Kippenhahn & Schlüter 1957;Kuperus & Raadu 1974), and neutral atoms are supported by the frictional force between them and the plasma (Low et al 2012). Prominences are dynamic structures, displaying motions of various kinds, such as turbulence (e.g.…”
Section: Introductionmentioning
confidence: 99%